Transportal Tibiotalocalcaneal Nail Ankle Arthrodesis: A Systematic Review of Initial Series - Darius Luke Lameire MD; Hassaan Abdel Khalik MMI, MD; Christopher Del Balso MBBS, MSc, FRCSC; Timothy Daniels MD, FRCSC; Mansur Halai MD, FRCSC (Foot & Ankle Orthopaedics, 2023)
Background: There is currently a scarcity of information and consensus for transportal (arthroscopic or fluoroscopic) joint preparation during tibiotalocalcaneal (TTC) fusion, and therefore this review aims to summarize the available techniques and to evaluate the outcomes after this procedure. Methods: A systematic electronic search of MEDLINE, EMBASE, and Web of Science was performed for all English-language studies published from their inception to April 4, 2022. All articles addressing arthroscopy in TTC nailing were eligible for inclusion. The PRISMA Checklist guided the reporting and data abstraction. Descriptive statistics are presented. Result: A total of 5 studies with 65 patients were included for analysis. All studies used arthroscopic portals for tibiotalar and subtalar joint preparation (in 4 studies) prior to TTC nailing, with 4 studies using an arthroscope and 1 study using fluoroscopy. The overall major complication rate was 13.8%; however, there was only 1 instance of deep wound infection (1.5%) and 4 instances of surgical site infections (6.2%). Full fusion was achieved in 86% of patients with an average time to fusion of 12.9 weeks. The mean American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot score preoperatively was 34.0 and postoperatively was 70.5. Conclusion: Although limited by the number of studies, transportal joint preparation during TTC nail ankle fusion is associated with good rates of complications and successful fusion. Level of Evidence: Level III, systematic review of Level III-IV studies.